2009
DOI: 10.1165/rcmb.2008-0201oc
|View full text |Cite
|
Sign up to set email alerts
|

WNT5A Is a Regulator of Fibroblast Proliferation and Resistance to Apoptosis

Abstract: Usual interstitial pneumonia (UIP) is a specific histopathologic pattern of interstitial lung fibrosis that may be idiopathic or secondary to autoimmune diseases and environmental exposures. In this study, we compared gene expression patterns in primary fibroblasts isolated from lung tissues with UIP histology and fibroblasts isolated from lung tissues with normal histology using expression microarrays. We found that WNT5A was significantly increased in fibroblasts obtained from UIP lung tissues compared with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
179
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 198 publications
(191 citation statements)
references
References 47 publications
(44 reference statements)
8
179
2
Order By: Relevance
“…Vinculin was used as loading control for chart and statistics. (Vuga et al 2009). It is perhaps relevant that non-canonical Wnt5A signaling, an important characteristic of IPF (Willis et al 2006), regulates epithelial-mesenchymal transition (EMT) in metastatic lung cancer (Gujral et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Vinculin was used as loading control for chart and statistics. (Vuga et al 2009). It is perhaps relevant that non-canonical Wnt5A signaling, an important characteristic of IPF (Willis et al 2006), regulates epithelial-mesenchymal transition (EMT) in metastatic lung cancer (Gujral et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…13 Canonical Wnt signaling is normally strictly regulated, and one control mechanism is non-canonical signaling (induced by, e.g., Wnt5a), which inhibits gene expression. 29 The involvement of Wnt signaling in the development of fibrosis can therefore be expected by several reasons, and has previously been described 17,18,30 and reviewed. 31 Interestingly, the number of cells positive for Wnt3a and β-catenin did not correlate completely, as Wnt3a was normalized at 3w, whereas β-catenin was increased, which may indicate an effect of other Wnt:s, not investigated within this study.…”
Section: Endothelial Stress and Pulmonary Fibrosismentioning
confidence: 99%
“…In addition, several studies have shown the importance of Wnt signaling in pulmonary fibrosis. 17,18 The aim of the present study was to identify a mechanism for the development of pulmonary fibrosis following subcutaneous bleomycin administration. For greater accuracy, we used histology enabling us to specifically investigate the lung parenchyma.…”
mentioning
confidence: 99%
“…In IPF lungs, the WNT/β-catenin signaling pathway with its main canonical signal transducers, Gsk-3β and β-catenin, has been detected to be significantly activated mainly in hyperplastic type II epithelial cells, with nuclear translocation of β-catenin and over-expression of its response genes, like cyclin D1 and matrix metalloprotease-7 41,42 . Likewise, WNT5A has been found significantly increased in IPF fibroblasts, which seem to play a role in fibroblast expansion through non-canonical WNT/ beta-catenin pathway 43 . Moreover, increased WNT signaling pathway components (such as the coreceptor LRP5 and its paralog LRP6) are associated with rapid progression of IPF 44 .…”
Section: Putative Sequence Of the Cellular And Molecular Pathogenic Mmentioning
confidence: 92%